Soil moisture response to rainfall on the Chinese Loess Plateau after a long‐term vegetation rehabilitation. Issue 12 (1st June 2018) - Jin, Zhao; Guo, Li; Lin, Henry; Wang, Yunqiang; Yu, Yunlong; Chu, Guangcheng; Zhang, Jing
Abstract: The Chinese Loess Plateau (CLP) is a unique Critical Zone with deep loess deposits, where soil moisture is primarily replenished by seasonal monsoon rainfall. However, the role of vegetation, coupled with complex topography, on rainwater infiltration on the CLP, especially after long‐term revegetation for controlling erosion, is inadequately quantified. Over the growing season of 2016, we monitored soil moisture at the 30‐min interval at 5 depths (10, 20, 40, 60, and 100 cm) in an afforested catchment and a nearby catchment with natural regrowth of grasses. Two monitoring sites were established in each catchment, one in the downhill gully and the other in the uphill slope. We found that vegetation, topography, and rainfall attributes together determined rainwater infiltration and soil moisture replenishment. An accumulated rainfall amount of 9 mm was required to trigger soil moisture response at 10‐cm depth at the 2 grassland sites and the forestland uphill‐slope site whereas 14 mm of rainfall was required for the forestland gully site covered by dense undergrowth and trees. Rainfall events with larger sums and higher peak intensities permitted rainwater infiltration to deeper soil depths. However, no rain recharged soil moisture to 100‐cm depth during the monitoring period. The forestland uphill‐slope site showed the deepest wetting depth (up to 60‐cm depth), fastest wetting‐front velocity (up to 4 cm/hr below 10‐cm depth), and the most significant soil moisture increase (up to 15% cm 3 cm −3 increase at 10‐cm depth) after rainfall in the growing season. The grassland gully site had the highest soil water storage, whereas soil moisture was depleted the most at the forestland gully site. Findings of this study reveal the transient dynamics of soil moisture after rainfall on the CLP, which signifies the role of revegetation on rainwater infiltration in the loess Critical Zone.